Dental and Oral Health Behaviour of Social and Political Sciences Student - Deshinta, Aulia; Selvia, Mega; W, Levina Gita; F.M, Ekky Nur; Safira V, Yasmin; N, Nadiyya Nurul; Azizah, Nur; Kusumo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: To find out the behaviour of Social And Political Sciences students from Universitas Airlangga on dental and oral health. Method: This study was a quantitative descriptive research. Information was obtained through an online questionnaire about behaviours related to dental and oral health. Results: The behaviour of Social And Political Sciences female students related to maintaining oral health was better (95.8%) compared to Social And Political Sciences students (90.9%). There was 94.9% of Social And Political Sciences students at Universitas Airlangga have good behaviour towards oral health with an average score of 12.4% (score> 10) while 5.1% of other students have an average score of 8.3 (score <10) indicating bad behaviour towards dental health and mouth. Conclusion: The overall behaviour of Universitas Airlangga’s of Social And Political Sciences students in maintaining oral hygiene and health is included in both categories. Even though they did not receive formal education about oral health, Universitas Airlangga of Social And Political Sciences students were able to maintain their oral health well.